Analysis of Amber Samples by LIBS and Chemometrics Methods - Flores, Teresa (2023)
We analyzed amber samples from the the Baltic region and Mexico, as well as imitation amber, in order to develop an analytical method allowing to discriminate between different samples causing little or no damage. We propose a two-step method that involves the use of Laser Induced Breakdown Spectroscopy (LIBS) to obtain spectra, and Discriminant Analysis to analyze the resulting data. We studied the damage caused to the samples using confocal optical microscopy.